1992
DOI: 10.1111/j.1469-8986.1992.tb01689.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison between Two Methods for Assessing Heartbeat Perception

Abstract: In this study two methods assessing heartbeat perception ability were compared. Subjects (N = 64) completed Schandry's (1981) mental tracking task and Störmer's (1988) heartbeat discrimination procedure (based on Whitehead, Drescher, Heiman, & Blackwell, 1977). In addition, subjects were tested on their ability to estimate the duration of time intervals. A high degree of correspondence was found between the two heartbeat perception tasks for the extreme groups of very good and very poor perceivers, but a low d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
2

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 13 publications
4
82
2
Order By: Relevance
“…In contrast, a lower HR in habitually good HR perceivers was reported by Schandry [5], but this finding was not replicated by Knoll and Hodapp [21]. Two recent studies indicate that HR and HR reactivity are of only minor importance for good HR estima tion, while cardiac contractility is more rele vant [22,23].…”
Section: Discussioncontrasting
confidence: 38%
“…In contrast, a lower HR in habitually good HR perceivers was reported by Schandry [5], but this finding was not replicated by Knoll and Hodapp [21]. Two recent studies indicate that HR and HR reactivity are of only minor importance for good HR estima tion, while cardiac contractility is more rele vant [22,23].…”
Section: Discussioncontrasting
confidence: 38%
“…Prior interoceptive research demonstrates a relationship between objective performance on these two heartbeat tests (e.g. Garfinkel, et al, 2015;Hart, et al, 2013;Knoll & Hodapp, 1992), however this relationship is not always observed, especially in smaller samples (e.g. Phillips,…”
Section: Discussionmentioning
confidence: 99%
“…It has good test-retest reliability (up to .81) and correlates highly with other heartbeat detection tasks. [51] Former studies [28,[52][53][54] could show that heartbeat perception tasks based on the discrimination method are well validated and reliable (Cronbach's a .69-.90).…”
Section: Data Analysesmentioning
confidence: 99%